Glycans and Glycan-Binding Proteins as Regulators and Potential Targets in Leukocyte Recruitment - Krautter, Franziska; Iqbal, Asif J. (Frontiers in Cell and Developmental Biology, 2021)
Leukocyte recruitment is a highly controlled cascade of interactions between proteins expressed by the endothelium and circulating leukocytes. The involvement of glycans and glycan-binding proteins in the leukocyte recruitment cascade has been well characterised. However, our understanding of these interactions and their regulation has expanded substantially in recent years to include novel lectins and regulatory pathways. In this review, we discuss the role of glycans and glycan-binding proteins, mediating the interactions between endothelium and leukocytes both directly and indirectly. We also highlight recent findings of key enzymes involved in glycosylation which affect leukocyte recruitment. Finally, we investigate the potential of glycans and glycan binding proteins as therapeutic targets to modulate leukocyte recruitment and transmigration in inflammation.